Integrating Religion and Spirituality into Clinical Practice - René Hefti (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The present Special Issue Book is a collection of scientific articles from the European Conferences of Religion, Spirituality and Health in 2014 (Malta) and 2016 (Gdansk). The overall theme is "Integrating Religion and Spirituality into Clinical Practice". Studies are grouped under four main topics: Religion and Spirituality in Patient Care, Spirituality in Physical and Mental Disease, Health Care Professionals and Spirituality, and Faith-Based Services and Programs in Health Care. The chapters illustrate the broad range of topics presented.